Student Motivation in the Classroom: Practical Techniques and Strategies - Adhikari, Narayan Prasad; Budhathoki, Jhupa Kumari; Adhikari, Sharad (Cognition, 2025)
The main objective of this study is to find out the practical techniques and strategies for student motivation in the classroom. This study is based on literatures review and presented in descriptive way. This article discusses numerous motivational techniques and strategies aimed to improve student's learning. It is found that supporting student motivation in the classroom is a challenging yet essential task for teachers. Enhancing classroom motivation is vital for creating a productive learning environment. Effective and practical techniques and strategies can significantly enhance students’ motivation and academic performance. It gives teachers the useful resources they need to motivate and inspire their students. It is argued that encouraging students to perform in the classroom should come from both intrinsic and extrinsic sources, but that encouraging students to learn and achieve will ultimately come from an intrinsic source will be extremely important. It is important that motivated students should work toward being autonomous learners, using self-regulated learning techniques, and accepting accountability for their own education. This article provides insights into practical strategies that help maximize student motivation and encourage academic accomplishment, from creating an optimal learning environment to putting new methods of instruction into practice.